2009
DOI: 10.21273/hortsci.44.1.106
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment of Mineral Elements in the Culture Medium for the Micropropagation of Three Vriesea Bromeliads from the Brazilian Atlantic Forest: The Importance of Calcium

Abstract: Many different species of Bromeliaceae are endangered and their conservation requires specific knowledge of their growth habits and propagation. In vitro culture of bromeliads is an important method for efficient clonal propagation and in vitro seed germination can be used to maintain genetic variability. The present work aims to evaluate the in vitro growth and nutrient concentration in leaves of the epiphyte bromeliads Vriesea friburguensis Mez, Vriesea hierogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 28 publications
0
8
0
10
Order By: Relevance
“…Also, it plays an important role in the synthesis and activity of several crucial enzymes (George, 1993). Studies on some plants showed that Ca 2+ is an essential factor for protocorm formation (Mitra et al, 1976), adventitious bud formation (Tanimoto and Harada, 1986), increase the mean number of somatic embryos (Jansen et al, 1990), somatic embryogenesis (Timmers et al, 1996), formation of meristemoids (Capitani and Altamura, 2004), and facilitated the uptake of some nutrients (Aranda-Peres et al, 2009). These facts show that why Ca 2+ is critical for improving some disorders in plants (Singha et al, 1990) and is necessary for plant growth and development.…”
Section: Resultsmentioning
confidence: 99%
“…Also, it plays an important role in the synthesis and activity of several crucial enzymes (George, 1993). Studies on some plants showed that Ca 2+ is an essential factor for protocorm formation (Mitra et al, 1976), adventitious bud formation (Tanimoto and Harada, 1986), increase the mean number of somatic embryos (Jansen et al, 1990), somatic embryogenesis (Timmers et al, 1996), formation of meristemoids (Capitani and Altamura, 2004), and facilitated the uptake of some nutrients (Aranda-Peres et al, 2009). These facts show that why Ca 2+ is critical for improving some disorders in plants (Singha et al, 1990) and is necessary for plant growth and development.…”
Section: Resultsmentioning
confidence: 99%
“…Aranda -Peres et al (2009) observed the highest data for dry and fresh masses of Vriesea friburguensis, V. unilaterais and V. hieroglyphica (Bromeliaceae) in vitro cultured, when used 12 mM Ca in Murashige and Skoog (MS) media, and Aechmea blanchetiana plantlets cultured in vitro in MS modified media with 9.38 mM Ca had an increase in fresh and dry masses (Kanashiro et al, 2009). Silver vase bromeliad did not show visual symptoms of calcium deficiency in leaves (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Quanto à composição do meio nutritivo, observouse que o crescimento das plantas de N. minutum ocorreu mais satisfatoriamente no tratamento MS/2 em comparação aos demais utilizados no presente trabalho. Diluições do meio MS em sua formulação original têm sido utilizadas na micropropagação de bromélias como relatado para V. hieroglyphica KERBAUY, 1994), Ananas comosus (L.) Merril cultivar Smooth Cayene (TAMAKI et al, 2007), V. friburgensis Mez e V. unilateralis (Baker) Mez (ARANDA-PEREZ et al, 2009). Estudos recentes com N. minutum mostraram que essa espécie sobrevive por pelo menos 180 dias sob deiciência de nitrogênio, fósforo e potássio, indicando capacidade de tolerar ambientes, nutricionalmente, mais diluídos (ANDRADE; TAMAKI, 2012).…”
Section: Msunclassified